1982
DOI: 10.1002/ejsp.2420120310
|View full text |Cite
|
Sign up to set email alerts
|

Right–left political ideologies and attribution of the causes of poverty

Abstract: The present research is a continuation of other recent studies (Sinha, Jain and Pandey, 1980;Pandey, Kakkar, and Bohra, 1982) related to attributions of the causes of poverty. In that study income and ownership of means of production were considered major determinants of an individual's perspective with respect to attribution processes. The role of perspective in attribution processes has also been emphasized by several others (Mannheim, 1960;Kelley, 1973).This study originated from our conviction that the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 4 publications
5
23
0
1
Order By: Relevance
“…Feather (1974) replicated Feagin's (1972) study and found that although Australians were less likely than Americans to offer individualistic reasons their explanations were affected by similar variables. Similar findings have been reported by other researchers-in India (Pandey et al, 1982); and in the UK (Furnham, 1982). In contrast, Lamarche and Tougas (1979) did not observe any influence of demographic factors on French-speaking Canadians who incidentally preferred structural reasons to individualistic ones.…”
Section: Perceptions and Imagessupporting
confidence: 82%
See 1 more Smart Citation
“…Feather (1974) replicated Feagin's (1972) study and found that although Australians were less likely than Americans to offer individualistic reasons their explanations were affected by similar variables. Similar findings have been reported by other researchers-in India (Pandey et al, 1982); and in the UK (Furnham, 1982). In contrast, Lamarche and Tougas (1979) did not observe any influence of demographic factors on French-speaking Canadians who incidentally preferred structural reasons to individualistic ones.…”
Section: Perceptions and Imagessupporting
confidence: 82%
“…In contrast, Lamarche and Tougas (1979) did not observe any influence of demographic factors on French-speaking Canadians who incidentally preferred structural reasons to individualistic ones. Political belief also seems to be an important factor with right-wingers preferring individualistic reasons to structural ones (Furnham, 1982;Pandey et al,1982).…”
Section: Perceptions and Imagesmentioning
confidence: 97%
“…Conservatives tend to offer individualistic explanations, which places responsibility on the behavior of the person, while Labour voters tend to offer societal explanations which places responsibility on external social and economic forces" p. 116). Thus, Furnham and Henderson's observations match those of different authors (e.g., Echebarria-Echabe & Gonzales-Castro, 1993;Gaffié, Marchand, & Cassagne, 1997Pandey, Sinha, Prakash, & Tripathi, 1982) and confirm Moscovici's intuition that: "in the societies we inhabit today, personal causality is a right-wing explanation and situational causality is a left-wing explanation" (1984, p. 50). …”
supporting
confidence: 84%
“…For example studies by Feagin (1972) and Townsend (1979) found that North American countries more often explained poverty in individualistic terms that in situational terms. On the contrary, researchers in India (Pandey et al, 1982) found that participants offered situational explanations more often to explain the problems such as poverty.…”
Section: Attribution Theorymentioning
confidence: 94%